Theory of Risk and Risk Management - Juma, Mussa Charles (Theory of Risk and Risk Management, Edition 1, 2024)
Risk has far-reaching implications, both financial and non-financial. To select the proper mode of treatment, each business unit must assess the risk in terms of its impact on attaining the strategic objectives in both monetary and non-monetary terms. The amount to which major risks are discovered, measured, and correctly managed utilizing the optimal combination of risk treatment procedures determines the organization's success in meeting its objectives. Climate change, technology and other emerging risks have increased the complexity of risk frequency and severity trends, necessitating the adoption of complicated approaches involving artificial intelligence and machine learning in their assessment in order to apply the right treatment method. The purpose of this book is to provide a critical analysis of risk theory and risk management. The book is divided into eight chapters with sections and subsections. Chapter 1 explores the company's key dependencies, core processes, stakeholder expectations, business and strategic objectives, and the risks associated with them. It also looks at the company's risk culture, risk attitude, risk profile, risk capacity, and risk appetite. It highlights the components of risk and the risk spectrum in relation to the level of knowledge about the future situation of an event to occur. A thorough review of decision theory is given in Chapter 2, which also examines its models, foundations, and real-world applications. Real-world case studies are used to analyse decision-making contexts, criteria, and processes, highlighting the importance of decision theory in making well-informed decisions. Readers may properly examine complex decision-making scenarios thanks to the discussion of key concepts, theories, and tools. This chapter gives decision-makers the information and abilities they need to make wise decisions by fusing theoretical frameworks with real-world insights. The third chapter explores the problems and logic behind risk classification. The significance of the primary risk categories—financial and non-financial, strategic, tactical, operational, and compliance risks, systemic and non-systemic risks, particular and fundamental risks, and insurable and non-insurable risks—is evaluated. The tenets and reasoning behind risk classification schemes are thoroughly investigated. There is a thorough discussion of the risks, challenges, and limitations of risk taxonomy. The effects of risk, both financial and non-financial, are examined in Chapter 4. In order to model hazards, it looks at risk measures, discrete and continuous loss distribution functions, and the characteristics of probability distribution functions. Both individual and collective risk models are evaluated. Parameter estimations and goodness-of-fit tests are thoroughly examined in this presentation of the risk modelling approach for insurance claims. The application of machine learning and artificial intelligence to risk assessment and management is examined in this chapter. The concept of risk management and the risk management method are examined from a number of angles in Chapter 5. In-depth research is done on risk assessment, measurement, and treatment techniques. There is also discussion of various methods for communicating and reporting hazards. A detailed description of the risk management framework and its elements is provided. The chapter concludes with an analysis of risk management performance after going over the fundamentals of risk management and the justifications for engaging in risk management activities. Tools for identification, risk assessments, and risk management strategies are thoroughly examined. Additionally, risk management guidelines are provided. In order to respond to a crisis and lessen its effects, Chapter 6 looks at the creation of business continuity plans, crisis management plans, incident management plans, and disaster recovery plans. The chapter discusses business dependencies and vulnerabilities, the lifecycle of business continuity management, the causes of business discontinuity, and its effects. Additionally, it looks at and creates strategies for resilience and disaster recovery, incident and crisis management, and the life cycle of business continuity management. The structure and requirements for business continuity are thoroughly reviewed. The ideas, tenets, perspectives, and importance of risk management are examined in Chapter 7. It discusses financial developments in derivative products as well as the evolution of risk management from active to proactive approaches. It looks at how technological development and climate change affect risk management initiatives. Finally, chapter 8 examines corporate governance concepts and the development of a corporation. It looks at stakeholders and how they relate to the company. It examines the roles played by the board of directors, risk managers, and auditors, among other components of the governance system. There is extensive discussion on the nature, tenets, standards, and objectives of the corporate governance code. This book is intended for third-year students pursuing bachelor's degree and master's degrees students in risk management, and insurance. If they want to brush up on their knowledge, risk management practitioners and professionals will also find this book to be helpful.